Fluids, vasopressors, and acute kidney injury after major abdominal surgery between 2015 and 2019: a multicentre retrospective analysis. (September 2022) - Chiu, Catherine; Fong, Nicholas; Lazzareschi, Daniel; Mavrothalassitis, Orestes; Kothari, Rishi; Chen, Lee-lynn; Pirracchio, Romain; Kheterpal, Sachin; Domino, Karen B.; Mathis, Michael; Legrand, Matthieu
Abstract: Background: Practice patterns related to intraoperative fluid administration and vasopressor use have potentially evolved over recent years. However, the extent of such changes and their association with perioperative outcomes, such as the development of acute kidney injury (AKI), have not been studied. Methods: We performed a retrospective analysis of major abdominal surgeries in adults across 26 US hospitals between 2015 and 2019. The primary outcome was AKI as defined by the Kidney Disease Improving Global Outcomes definition (KDIGO) using only serum creatinine criteria. Univariable linear predictive additive models were used to describe the dose-dependent risk of AKI given fluid administration or vasopressor use. Results: Over the study period, we observed a decrease in the volume of crystalloid administered, a decrease in the proportion of patients receiving more than 10 ml kg −1 h −1 of crystalloid, an increase in the amount of norepinephrine equivalents administered, and a decreased duration of hypotension. The incidence of AKI increased between 2016 and 2019. An increase of crystalloid administration from 1 to 10 ml kg −1 h −1 was associated with a 58% decreased risk of AKI. Conclusions: Despite decreased duration of hypotension during the study period, decreased fluid administration and increased vasopressor use were associated with increased incidence of AKI. Crystalloid administration below 10 ml kg −1 h −1 was associated with an increased risk of AKI. Although no causality can be concluded, these data suggest that prevention and treatment of hypotension during abdominal surgery with liberal use of vasopressors at the expense of fluid administration is associated with an increased risk of postoperative AKI.